2023
DOI: 10.1146/annurev-publhealth-052220-124030
|View full text |Cite
|
Sign up to set email alerts
|

Cancers Attributable to Modifiable Risk Factors: A Road Map for Prevention

Abstract: The implementation of primary and secondary preventive strategies is based on the evidence generated by cancer epidemiology, where the identification of risk factors and the description of their prevalence are fundamental to derive estimates on the burden of cancer from different etiologies, typically expressed as the population attributable fraction, which corresponds to the proportion of a cancer that may be prevented by controlling a given risk factor. However, even when cancer finds its etiology in modifia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…Next to the dramatic reduction in the use of aromatic amines in Italian industries starting around 1955 [ 69 , 70 ], the banning of asbestos in the early 1990s should be noted. The high proportions of mesothelioma cases and deaths calculated for the year 2020 were not unexpected; our results are, indeed, consistent with the prediction by Oddone and coworkers, who expected 1122 cases of mesothelioma attributed to asbestos in 2021 in Italy, despite not focusing on occupational exposure [ 71 ]. Indeed, the risk of mesothelioma persists throughout the lifespan of exposed subjects [ 72 ], and, while the banning prevented from the further use of asbestos, many asbestos residuals still need to be replaced from workplaces [ 73 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Next to the dramatic reduction in the use of aromatic amines in Italian industries starting around 1955 [ 69 , 70 ], the banning of asbestos in the early 1990s should be noted. The high proportions of mesothelioma cases and deaths calculated for the year 2020 were not unexpected; our results are, indeed, consistent with the prediction by Oddone and coworkers, who expected 1122 cases of mesothelioma attributed to asbestos in 2021 in Italy, despite not focusing on occupational exposure [ 71 ]. Indeed, the risk of mesothelioma persists throughout the lifespan of exposed subjects [ 72 ], and, while the banning prevented from the further use of asbestos, many asbestos residuals still need to be replaced from workplaces [ 73 ].…”
Section: Discussionsupporting
confidence: 91%
“…The reduced figures of the AF of occupation-related cancers in Italy are mainly attributable to the progressive reduction in the prevalence of exposure to the main occupational carcinogens. The decreasing proportion of workers exposed to asbestos in recent years is likely to further reduce these numbers in the near future [ 71 ]. The reinforcement of occupational health recommendations, including the promotion of PPE use and the education about health hazards and their prevention at the workplace, are a key point to lower the number of workers exposed to occupational carcinogens such as wood dust, nickel, and UV radiation, whose control still needs improvement.…”
Section: Discussionmentioning
confidence: 99%
“…PAFs were highest for suicide attempts (41%) and self-harm (39%) and more modest for depression (21%). For perspective, tobacco smoking accounts for 24% of cancers in US men, and hypertension accounts for 23% of myocardial infarctions globally . Child maltreatment was found to account for more than 184 000 years of healthy life lost through mental ill health in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient air pollutants are a complex mixture of suspended particulate matters (PMs) and gases, such as PM with an aerodynamic diameter less than 2.5 μm (PM 2.5 ) and less than 10 μm (PM 10 ), nitrogen dioxide (NO 2 ), carbon monoxide (CO), sulfur dioxide (SO 2 ), and ozone (O 3 ) (Shubham et al 2022 ). Air pollution has been reported to be associated with chronic respiratory diseases (Annesi-Maesano et al 2021 ), cardiovascular diseases (de Bont et al 2022 ), stroke (Verhoeven et al 2021 ), and cancers (Collatuzzo and Boffetta 2023 ), which is also a major contributor to global mortality (Cohen et al 2017 ). In recent years, a growing body of evidence has shown that increased exposure to ambient air pollutants corresponds to an increased risk of CKD (Bowe et al 2017 , 2018 ; Lin et al 2018 , 2020a ; Blum et al 2020 ; Yang et al 2017 ; Wang et al 2020 ), renal function decline (Bowe et al 2017 , 2018 ; Wang et al 2020 ; Chang et al 2022 ), and ESRD (Bowe et al 2017 , 2018 ; Lin et al 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%